(untitled) (Journal of Environmental Bioremediation and Toxicology, 2023)
Dyes are one of the hazardous chemicals found in wastewater produced by textile and allied industries that need to be removed from the wastewater before it is released into water bodies. The sorption efficiency of raw groundnut shell (RGS), an agricultural waste, was tested on methylene blue (MB) dye through a batch adsorption experiment. Physicochemical analysis of the RGS indicated good biosorbent properties. Fourier transform infrared (FTIR) spectroscopy analysis of the RGS revealed the presence of heterofunctional groups. The effect of various biosorption parameters such as initial dye concentration, contact time, and biosorbent dosage was systematically investigated. The quantity of MB adsorbed increased as the initial concentration and contact time increased and decreased with an increase in biosorbent dose. A maximum uptake capacity of 29.3 mg/g was recorded for 50 mg/L MB initial concentration. The equilibrium data from the batch adsorption experiments were fitted well into Freundlich isotherm and pseudo-second-order kinetic models. The results from this study indicate that RGS can serve as an alternative, low-cost, eco-friendly and efficient adsorbent for the removal of MB dye from wastewater.